2016
DOI: 10.1097/md.0000000000003504
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Model Using Inflammation- and Nutrition-Based Scores in Patients With Metastatic Gastric Adenocarcinoma Treated With Chemotherapy

Abstract: The outcomes of patients with metastatic gastric cancer (mGC) are poor. Recent studies have identified the prognostic impact of inflammatory response and nutritional status on survival for patients with gastric cancer. This study aims to create a prognostic model using inflammatory- and nutrition-based scores to predict survival in patients with mGC treated with chemotherapy.After institutional review board approval, patients who had mGC and were treated with chemotherapy from 2007 to 2012 at Kaohsiung Chang G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 28 publications
2
40
1
Order By: Relevance
“…This finding is in accordance with Cho et al, who also reported significantly higher chemotherapeutic disease control rate in metastatic advanced gastric cancer patients having low NLR, defined as less or equal to 3.0 [50]. Combined scores have been generated to evaluate the prognosis of metastatic gastric cancer as well [26].…”
Section: Nlr and Survival: Prognostic Implicationssupporting
confidence: 79%
See 4 more Smart Citations
“…This finding is in accordance with Cho et al, who also reported significantly higher chemotherapeutic disease control rate in metastatic advanced gastric cancer patients having low NLR, defined as less or equal to 3.0 [50]. Combined scores have been generated to evaluate the prognosis of metastatic gastric cancer as well [26].…”
Section: Nlr and Survival: Prognostic Implicationssupporting
confidence: 79%
“…The respective two-year survival rates were 52% vs. 16% vs. 3%. The ROC curve analysis confirmed that the novel score has higher informativity than any of its components [26].…”
Section: Gastric Cancer 180mentioning
confidence: 49%
See 3 more Smart Citations